Effect of TiO2 on the sintering behavior and microstructure of stoichiometric spinel (MgAl2O4) - Hassen, Baker F. (Iraqi Journal of Physics, 2019)
In this work, magnesium aluminate spinel (MA) (MgO 28 wt%, Al2O3 72 wt%) stoichiometric compound , were synthesized via solid state reaction (SSR) Single firing stage, and the impact of sintering on the physical properties and thermal properties as well as the fine structure and morphology of the ceramic product were examined. The Spinel samples were pressed at of (14 MPa) and sintering soaking time (2h). The effect of adding oxide titania (TiO2) was studied. The obtained powders were calcined at a temperature range of 1200 and 1400 °C. The calcined samples spinel were characterized by XRD, it showed the presence of developed spinel phase end also showed that the best catalyst is titania. The SEM image showed the high sintering temperature increased the regularity of the grain growth, as well as minutes from the acquisition of the spherical shape of the minutes spinel.